Growth and morphometrics in the New Zealand sea urchin Pseudechinus huttoni (Echinoidea: Temnopleuridae) - Selena Kirby; Miles D. Lamare; Mike. F. Barker (New Zealand Journal of Marine and Freshwater Research, 2006)
We examined somatic growth in the New Zealand sea urchin, Pseudechinus huttoni. This species normally inhabits the continental shelf, but in the New Zealand fiords can be found at shallower depths. These shallower populations provided an opportunity to quantify growth of these deep water sea urchins using chemical tag recapture techniques. Growth was modelled in three Doubtful Sound populations and varied spatially, with maximum test diameter (TD) and maximum growth rates ranging from 33.8 to 42.7mm TD and 2.9mm yr ‐1 to 23.9mm yr ‐1 , respectively. Size‐at‐age modelling suggests that P. huttoni is c. 5–15mm TD at 1 year, 20–30mm TD at 4 years, and adults approach a maximum size of 30–40 mm TD after 6 to 11 years. Growth in continental shelf populations was inferred from measured growth in the fiord population by comparing population statistics (size structures, mean size), morphometrics, and nutritional status among both habitats. Our results indicate that growth of P. huttoni populations on continental shelves varies spatially (with depth), but is within the range of growth measured in the Doubtful Sound populations. A generalised growth model for P. huttoni based on the three Doubtful Sound populations is described by the Brody‐Bertalanffy equation S t = 42.17(1–0.99e (‐0.229t) ).